New Method for the Approximation of Corrected Calcium Concentrations in Chronic Kidney Disease Patients. Issue 1 (February 2016) - Kaku, Yoshio; Ookawara, Susumu; Miyazawa, Haruhisa; Ito, Kiyonori; Ueda, Yuichirou; Hirai, Keiji; Hoshino, Taro; Mori, Honami; Yoshida, Izumi; Morishita, Yoshiyuki; Tabei, Kaoru
Abstract: The following conventional calcium correction formula (Payne) is broadly applied for serum calcium estimation: corrected total calcium (TCa) (mg/dL) = TCa (mg/dL) + (4 – albumin (g/dL)); however, it is inapplicable to chronic kidney disease (CKD) patients. A total of 2503 venous samples were collected from 942 all‐stage CKD patients, and levels of TCa (mg/dL), ionized calcium ([iCa 2+ ] mmol/L), phosphate (mg/dL), albumin (g/dL), and pH, and other clinical parameters were measured. We assumed corrected TCa (the gold standard) to be equal to eight times the iCa 2+ value (measured corrected TCa). Then, we performed stepwise multiple linear regression analysis by using the clinical parameters and derived a simple formula for corrected TCa approximation. The following formula was devised from multiple linear regression analysis: Approximated corrected TCa (mg/dL) = TCa + 0.25 × (4 − albumin) + 4 × (7.4 − p H) + 0.1 × (6 − phosphate) + 0.3. Receiver operating characteristic curves analysis illustrated that area under the curve of approximated corrected TCa for detection of measured corrected TCa ≥ 8.4 mg/dL and ≤ 10.4 mg/dL were 0.994 and 0.919, respectively. The intraclass correlation coefficient demonstrated superior agreement using this new formula compared to other formulas (new formula: 0.826, Payne: 0.537, Jain: 0.312, Portale: 0.582, Ferrari: 0.362). In CKD patients, TCa correction should include not only albumin but also pH and phosphate. The approximated corrected TCa from this formula demonstrates superior agreement with the measured corrected TCa in comparison to other formulas.